Further records on the plant bug tribe Hallodapini (Hemiptera: Heteroptera: Miridae: Phylinae) in Asia, with proposition of two new species and a new synonymy - Duwal, Ram Keshari; Yasunaga, Tomohide; Tomokuni, Masaaki; Nakatani, Yukinobu; Hirowatari, Toshiya (Zootaxa, 2017)
A total of twelve species in five genera belonging to the phyline plant bug tribe Hallodapini are treated. Two new species are described from Indochina: Cleotomiris inthanon Duwal & Yasunaga sp. nov. (Thailand) and Cleotomiroides vietnamensis Duwal & Yasunaga sp. nov. (Vietnam). New distributional records are also presented for some known species of Hallodapus Fieber and Wygomiris Schuh. Hallodapus persimilis (Poppius) is proposed as a junior synonym of H. ravenar (Poppius). Illustrations of the endosoma for four species, including the new species, are presented. Digital images of the male genitalic structures are shown for nine species, including the two new species, and also female genitalic structures of the species of Cleotomiris Schuh, Cleotomiroides Schuh and Wygomiris Schuh, are provided. The immature forms are documented for the first time for Acrorrhinium inexpectatum (Josifov) and Wygomiris kaliyahae Yasunaga.